Prebiotic Activity Score of Rice Analogue Containing Porang (Amorphophallus onchophyllus) Glucomannan for Bifidobacterium longum FNCC 0210 and Lactobacillus acidophilus FNCC 0051 - Muktiadin Latifah; Yudi Pranoto; Eni Harmayani (Indonesian Association of Food Technologists, 2026)
Glucomannan from the porang tuber (Amorphophallus oncophyllus) was reported to have a prebiotic effect. The prebiotic effect of porang glucomannan used in a rice analog has never been studied. Glucomannan from porang tuber, k-carrageenan, and rice flour were used for producing rice analog in five ratios. The product was observed for its prebiotic activity score by enumerating the B. longum FNCC 0210, L. acidophilus FNCC 0051, and E. coli FNCC 0091 at 0, 24, and 48 h. The highest trend of rice analog prebiotic activity score was at GP15 rice (0.59+0.20) for B. longum FNCC 0210 and GP25 rice (0.91+0.60) for L. acidophilus FNCC 0051. The result indicates that a rice analog containing at least 10% porang glucomannan had a high prebiotic activity score. The ratio of porang glucomannan to k-carrageenan did not affect the prebiotic activity score of rice analog.